ENHANCING ENTREPRENEURIAL INTENTIONS AMONG NIGERIAN TERTIARY STUDENTS: THE ROLE OF ENTREPRENEURSHIP EDUCATION - Olufemi , Aladejebi (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
This paper examines the relationship between entrepreneurship education and entrepreneurial intentions among Nigerian tertiary students. The research surveyed 381 students from four institutions comprising of a university, a polytechnic, a college of education, and a satellite campus of a university. The survey revealed that many of the students hold a positive attitude towards entrepreneurship education and perceive the need for more practical examples in the classroom. The study further revealed that the behavioral component of their entrepreneurial attitude is positive, and many students have the intention to start their own businesses after graduation. The paper concludes that entrepreneurship education plays a critical role in boosting economic growth, creating jobs, and increasing wealth. Therefore, it is essential for tertiary institutions in Nigeria to incorporate it into their curricula.